Exogenous Melatonin Mitigates Acid Rain Stress to Tomato Plants through Modulation of Leaf Ultrastructure, Photosynthesis and Antioxidant Potential - Debnath, Biswojit (Molecules, 2018)
Acid rain (AR) is a serious global environmental issue causing physio-morphological changes in plants. Melatonin, as an indoleamine molecule, has been known to mediate many physiological processes in plants under different kinds of environmental stress. However, the role of melatonin in acid rain stress tolerance remains inexpressible. This study investigated the possible role of melatonin on different physiological responses involving reactive oxygen species (ROS) metabolism in tomato plants under simulated acid rain (SAR) stress. SAR stress caused the inhibition of growth, damaged the grana lamella of the chloroplast, photosynthesis, and increased accumulation of ROS and lipid peroxidation in tomato plants. To cope the detrimental effect of SAR stress, plants under SAR condition had increased both enzymatic and nonenzymatic antioxidant substances compared with control plants. But such an increase in the antioxidant activities were incapable of inhibiting the destructive effect of SAR stress. Meanwhile, melatonin treatment increased SAR-stress tolerance by repairing the grana lamella of the chloroplast, improving photosynthesis and antioxidant activities compared with those in SAR-stressed plants. However, these possible effects of melatonin are dependent on concentration. Moreover, our study suggests that 100-μM melatonin treatment improved the SAR-stress tolerance by increasing photosynthesis and ROS scavenging antioxidant activities in tomato plants.